PAI Teacher Digital Competency Based on Teaching Level - Budiyanti, Setia; Ulum, Itah Miftahul; Jaenudin, Amran; Aisyah, Siti (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The balance of technological developments in education must be carried out through digital competence. Digital competence is the ability to take advantage of digital technology to contribute more efficiently to work. The increase in the intensity of technology use during the pandemic cannot be generalized that teachers master learning technology. Digital competence has a broad study, not just technical. This study aims to diagnose the digital competence of PAI teachers after the pandemic. The DigiComp framework was adopted in this study to measure digital competence. The research design uses a quantitative approach, survey is applied as a research method. The research sample was PAI teachers throughout the city of Cirebon at various levels of education. The data were analyzed descriptively quantitatively. The results of the teacher's digital competence research cannot be said to meet. From the measured digital competence aspect, it was found that the percentage score was lacking, namely the security aspect and digital content creation. Increasing digital competence through regular training and guidance needs to be implemented.